Verification of the physical-chemical and microbiological conditions of homemade cakes sold by street vendors (Research, Society and Development, 2020)
The trade in food prepared and sold by street vendors in Brazil has grown significantly. However, this type of trade with their respective food products, can constitute a high risk to the health of consumers, since the people involved in these activities generally do not have a preparation for the proper handling of food and are unaware of the good practices of handling them. Given this, this study aimed to verify the physicochemical and microbiological conditions of homemade cakes sold by street vendors. For this, six cake samples were collected in the city of Codó-MA, obtained from random points. The cakes were analyzed for physical-chemical (moisture, lipids, proteins and ashes) and microbiological (total coliforms, coliforms at 45°C, Salmonella and fungi) parameters. The physicochemical aspects were as expected, except for the moisture that obtained a high content. Microbiological aspects showed that samples A and C are outside the standard defined by the legislation regarding the presence of coliforms at 45°C and Salmonella. Therefore, the consumption of these cakes poses a risk to the population and intervention measures must be taken.